Nitrogen analysis in tissue of three cultivars of rice - Mueller, Siegfried; Gomes, Algenor da Silva; Brauner, Jorge Luis (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was carried out during 1978/79 in an Albagualf soil, (Unidade de Mapemaneto Pelotas, Pelotas, RS, Brazil) and subsequent chemical analysis for N were made with the objective of determining: a. the appropriate time to teste for N; b. the appropriate plant parts to use; c. the extent of nitrogen variation within the plant as a function of time and d. the growth habit of the plant. Three cultivars of irrigated rice (Oryza sativa L.) were tested: EEA-406 (traditional cultivar). Bluebelle and BR/IRGA-409 (improved cultivars), and fertilized with five levels of N (0, 30, 60, 90 and 120 kg/ha de N). Plants were collected 28 days after emergence, at the time of the differenciation of the floral primordia, at flowering, and at harvest. The plants were separated, when possible, into lower leaves, upper leaves, stem, and panicle. Nitrogen determination was made for each part. Conclusion: a. bottom leaves and stems collected 28 days after emergence were the best plants to use to define critical levels of N. For the tradiditional cultivar EEA-406 the critical levels were, respectively, 3.42% end 1.72%. b. N concentration in the stems decreased with time. In both the upper and lower leaves N decreased from the first to the second sampling time, and increased at the third sampling time; at the fourth sampling time, N decreased in the upper leaves; c. within an identical sampling time, some plant parts of the cultivars Bluebelle and BR/IRGA-409 (improved cultivars) showed higher N concentrations than the cultivar EEA-406 (traditional cultivar).